Proposed Livin Digital Banking Product Development Strategy at PT. Bank Mandiri Tbk - Susanto, Haris; Safaria, Siti (Formosa Journal of Sustainable Research, 2024)
The purpose of this research is to develop a digital product development strategy for Livin by Mandiri. Research Context: In this study, the aim is to examine the development strategy of digital banking through SWOT analysis to overcome competition related to the development of digital banks. Importance of Research: Understanding how technology affects the development of digital banks and preparing strategies for digital bank development. Livin By Mandiri can improve operational efficiency, reduce operational costs, and increase employee productivity. The use of artificial intelligence (AI) technology and data analytics also helps provide more personalized and relevant banking services to customers. In addition, digital technology also allows Livin By Mandiri to expand its market share by reaching a wider customer segment, including millennials who are more likely to use technology-based banking services One of the strategic steps taken is to integrate digital technology in all lines of their banking business. In this transformation process, Livin By Mandiri does not only focus on developing application- based banking services or digital platforms, but also strives to strengthen its IT system, so that it can support banking operations as a whole